2022
DOI: 10.3390/ijerph19031677
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Moving Epidemic Method to Establish the Influenza Epidemic Thresholds and Intensity Levels for Age-Specific Groups in Hubei Province, China

Abstract: Background: School-aged children were reported to act as the main transmitter during influenza epidemic seasons. It is vital to set up an early detection method to help with the vaccination program in such a high-risk population. However, most relative studies only focused on the general population. Our study aims to describe the influenza epidemiology characteristics in Hubei Province and to introduce the moving epidemic method to establish the epidemic thresholds for age-specific groups. Methods: We divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The seasonal pattern was consistent with the results of other studies. 3 6 8 22 The highest incidence was observed in January 2019, which was also seen in other southern provinces of China, 27 28 relating to the temperature, humidity, economic and social activities and personal immunity at that time. We also found that the different seasonal trend among age groups.…”
Section: Discussionmentioning
confidence: 91%
“…The seasonal pattern was consistent with the results of other studies. 3 6 8 22 The highest incidence was observed in January 2019, which was also seen in other southern provinces of China, 27 28 relating to the temperature, humidity, economic and social activities and personal immunity at that time. We also found that the different seasonal trend among age groups.…”
Section: Discussionmentioning
confidence: 91%